General Quality of Life, Depression, and Anxiety: Differences According to Asthma Control - Sánchez Cervantes, Cintia Tamara (2021)
Objective. Compare quality of life (QoL) evaluated through the Quality of Life and Health Inventory, as well as depression and anxiety between subjects with controlled asthma and uncontrolled asthma. Method. This is a Cross-sectional, ex post facto study involving 149 Mexican adults with asthma. Results. Significant differences with moderate to large effect size were found in these sub-scales such as physical performance, isolation, free time, daily life, anxiety, and depression. The areas that correlated significantly and positively were daily life with isolation and free time, depression with isolation, and daily life. Subjects with uncontrolled asthma are affected in the QoL subscales related to physical and social activities, psychological treatments must attend to these areas.